Promoting adherence to organised physical activity among socially disadvantaged older people. Issue 2 (11th February 2021) - Nau, Tracy; Nolan, Genevieve; Smith, Ben J.
Abstract: Group-based physical activity (PA) in community-based settings represents a promising avenue for promoting healthy ageing, however, lower levels of adherence have been found to be associated with aspects of social disadvantage. Providers are in a key position to provide important insights about strategies to improve adherence, however, few studies have examined their perspectives. In this study, 30 community service providers were interviewed, and 42 older people participated in focus groups to identify actions perceived as effective for promoting adherence to organised PA, with a focus on factors relevant to older people experiencing socio-economic disadvantage, social isolation, living with a disability or from culturally and linguistically diverse backgrounds. Data were analysed thematically. Adherence barriers included deteriorating health, lack of belonging and loss of motivation. Helpful strategies for addressing deteriorating health included maintaining programme flexibility, facilitating access to health and other services, and supporting participants to adapt to acquired limitations. Belonging can be fostered by creating positive and inclusive experiences, ensuring safe and stigma-free environments, providing opportunities to forge personal connections and demonstrating care. Motivation may be enhanced by ensuring activities are of interest and functional benefit, programme settings are suitable and appealing, and enjoyment is prioritised. In conclusion, a range of strategies is likely to be necessary to mitigate risks to adherence and support continued participation in organised PA among socially disadvantaged older people.